Superconvergent patch recovery with constraints for three‐dimensional contact problems within the Cartesian grid Finite Element Method. (28th November 2019) - Navarro‐Jiménez, José M.; Navarro‐García, Héctor; Tur, Manuel; Ródenas, Juan J.
Summary: The superconvergent patch recovery technique with constraints (SPR‐C) consists in improving the accuracy of the recovered stresses obtained with the original SPR technique by considering known information about the exact solution, like the internal equilibrium equation, the compatibility equation or the Neumann boundary conditions, during the recovery process. In this paper the SPR‐C is extended to consider the equilibrium around the contact area when solving contact problems with the Cartesian grid Finite Element Method. In the proposed method, the Finite Element stress fields of both bodies in contact are considered during the recovery process and the equilibrium is enforced by means of the continuity of tractions along the contact surface.